Integrating Zircon Grain Shape Analysis with Detrital Mineral Geochronology and Geochemical Fingerprinting, Eucla Basin, Australia - Gartmair, Gisela Sandra (Curtin University, 2022)
Southern Australia's Eucla Basin is a world famous heavy mineral sands province. Little is understood about the basin's primary sediment provenance because of non-uniqueness in U-Pb age and Hf isotope signatures of likely source regions. This research integrates a geochronology-geochemistry-grain shape triple-characterisation approach to constrain sediment provenance, transportation, and recycling of Eucla Basin heavy mineral sands. The combined approach adds new insights and identifies the basin's underlying crystalline basement as the dominant heavy mineral source.